2018
DOI: 10.1177/1476718x18804848
|View full text |Cite
|
Sign up to set email alerts
|

Using dialogic reading strategies to promote social-emotional skills for young students: An exploratory case study in an after-school program

Abstract: As educators begin to understand the need for a social-emotional learning curriculum for young students, finding opportunities to implement a curriculum that supports students' social-emotional development is important. Research supports that using shared reading opportunities that are common in young students' in-school and out-of-school routines to embed social-emotional learning could have potential impact for young students' social emotional as well as academic development. This article describes an explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Oral language is supported through the use of dialogic reading strategies in which teachers use a variety of prompts to help children learn vocabulary, improve their listening comprehension, and take an increasingly active role in narrative retellings over repeated exposures to the book (Lonigan & Whitehurst, 1998). Beyond supporting language and literacy skills, conducting shared book reading sessions that are interactive in nature may also be a helpful strategy to promote young students’ social-emotional learning (Fettig et al, 2018), especially given that talking, listening, and engaging in conversations that reflect a child’s interests and preferences can positively impact children’s motivation and attitudes.…”
Section: Overview Of Shared Book Readingmentioning
confidence: 99%
“…Oral language is supported through the use of dialogic reading strategies in which teachers use a variety of prompts to help children learn vocabulary, improve their listening comprehension, and take an increasingly active role in narrative retellings over repeated exposures to the book (Lonigan & Whitehurst, 1998). Beyond supporting language and literacy skills, conducting shared book reading sessions that are interactive in nature may also be a helpful strategy to promote young students’ social-emotional learning (Fettig et al, 2018), especially given that talking, listening, and engaging in conversations that reflect a child’s interests and preferences can positively impact children’s motivation and attitudes.…”
Section: Overview Of Shared Book Readingmentioning
confidence: 99%
“…In subsequent research, dialogic reading has been found to develop young children's expressive vocabulary (see Hargrave & Senechal, 2000;Sim & Berthelsen, 2014), knowledge of narrative structure (Lever & Senechal, 2011), and to have positive effects on children's comprehension and decoding skills (Mol et al 2008). Furthermore, dialogic reading may be a helpful strategy to promote children's social-emotional learning (Fettig et al 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Finally, our work incorporates the fact that multimodal textual media such as graphical memes, podcasts, and data representations are key components of communication processes that should be included as part of the textual landscape in school curricular materials and assessments (Arya et al, 2020a; Kress, 2003). As such, we aimed to develop a reading assessment that involves the triangulation of multimodal texts that developing readers are encountering more frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging ongoing tensions related to what counts as key theoretical and empirical underpinnings within the area of reading studies, our study was built on previous work guided by sociocognitive scholarship that highlights the importance of (a) sociohistorical contextual matters that relate to conceptual assertions featured in texts and (b) the active involvement of participating students that are representative of the target population (Arya & Maul, 2021). Such active involvement aligns with research on social-emotional learning and the importance of incorporating students' interests and experiential knowledge in academic contexts (e.g., Fettig et al, 2018). We view such efforts to incorporate relevant, engaging topics as intertwined with the call for raising critical readers of various textual media.…”
Section: Introductionmentioning
confidence: 99%